Whole‐Genome Sequencing of a Single Viral Species from a Highly Heterogeneous Sample. (28th August 2015) - Han, Hee‐Sun; Cantalupo, Paul G.; Rotem, Assaf; Cockrell, Shelley K.; Carbonnaux, Martial; Pipas, James M.; Weitz, David A.
Abstract: Metagenomic studies suggest that only a small fraction of the viruses that exist in nature have been identified and studied. Characterization of unknown viral genomes is hindered by the many genomes populating any virus sample. A new method is reported that integrates drop‐based microfluidics and computational analysis to enable the purification of any single viral species from a complex mixed virus sample and the retrieval of complete genome sequences. By using this platform, the genome sequence of a 5243 bp dsDNA virus that was spiked into wastewater was retrieved with greater than 96 % sequence coverage and more than 99.8 % sequence identity. This method holds great potential for virus discovery since it allows enrichment and sequencing of previously undescribed viruses as well as known viruses. Abstract : Tröpfchenweise : Eine Plattform, die tröpfchenbasierte Mikrofluidik mit Computeranalyse verbindet, wurde entwickelt, um einzelne Virenspezies aus Mischungen zu isolieren und ihr Genom zu sequenzieren. Dies gelang für in Abwasser eingebrachtes SV40 mit über 96 % Abdeckung und 99.8 % Sequenzidentität. Das Verfahren kann auch zur Identifizierung unbekannter Viren genutzt werden.